The Contribution of Indonesian for Foreign Speaker (Bahasa Indonesia bagi Penutur Asing/BIPA) in Islamic Universities for Developing World Civilization - Siti Isnaniah (Universitas Islam Negeri Sunan Kalijaga, 2021)
Indonesian for Foreign Speaker or Bahasa Indonesia bagi Penutur Asing (BIPA) in Islamic Universities or PTKI grows rapidly, nationally and internationally, supported by strong regulation especially by Ministry of Religion Affair. It makes the existence of BIPA is able to contribute to develop world civilization, in accordance to the functions of language namely heuristics and referential. The objective of this research is to explain the contribution of BIPA in PTKI in developing the world civilization. The research used analytical descriptive method with qualitative approach. The sources of the data were informants from UIN Raden Mas Said Surakarta, UIN Syarif Hidayatullah Jakarta, UIN Tulungagung. They were teachers of BIPA in PTKI; managers of BIPA PTKI; International Office PTKI, managers of Indonesian Education Department in PTKI; documents, and events. The techniques collecting the data are in-depth interview, content analysis, and observation. The data were analyzed using interactive model by Miles & Huberman. The result of the study showed that BIPA PTKI was able to develop the world civilization. It was proven by the increasing numbers of foreign students who studied in PTKI, the delegated lectures of PTKI to teach delicate Indonesian culture, introduce moderate Islam to the world’s citizens so they can be accepted well by the world’s citizen. For this reason, Indonesia, especially PTKI, language, culture, and moderate Islam are well-known by the world’s citizens resulting the increasing numbers of cooperation and MoU between PTKI and many national and international institutions.